1998
DOI: 10.1152/jappl.1998.84.3.1024
|View full text |Cite
|
Sign up to set email alerts
|

Similar hypoxic ventilatory responses in sea-level natives and high-altitude Andean natives living at sea level

Abstract: High-altitude (HA) natives have blunted ventilatory sensitivities to hypoxia, and it is uncertain whether this blunting is reversible on migration to sea level (SL). To study this, the ventilatory sensitivities to hypoxia of HA natives residing near SL were compared with those of SL natives. Two studies were performed. In study A, 24 HA subjects who had lived above 3,000 m for an average of 14 yr and had been resident at SL for an average of 23 yr were compared with 23 SL controls. In study B, 25 HA subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0
3

Year Published

2000
2000
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 22 publications
3
13
0
3
Order By: Relevance
“…For example, humans raised at high altitude or born hypoxic because of cardiorespiratory diseases may acquire blunted hypoxic ventilatory responses during development (10,23,33,38,39). There is some debate as to whether this blunting is permanent (10,41), but many of these changes in respiratory control persist long after normoxic conditions are restored. Animal models support the conclusion that perinatal changes in O 2 levels induce developmental plasticity: lasting changes in the respiratory phenotype that can be elicited only during critical periods of development (cf.…”
mentioning
confidence: 99%
“…For example, humans raised at high altitude or born hypoxic because of cardiorespiratory diseases may acquire blunted hypoxic ventilatory responses during development (10,23,33,38,39). There is some debate as to whether this blunting is permanent (10,41), but many of these changes in respiratory control persist long after normoxic conditions are restored. Animal models support the conclusion that perinatal changes in O 2 levels induce developmental plasticity: lasting changes in the respiratory phenotype that can be elicited only during critical periods of development (cf.…”
mentioning
confidence: 99%
“…There is also conflict on the issue of the reversibility/irreversibility of blunting in adults who have returned to sea level. Older studies showed that chemosensitivity was not reversed by residence at sea level (36,61,64), whereas more recent studies in the Andes show at least partial reversibility of blunting in Peruvians born at HA but migrating to sea level (20,63). Interestingly, the acute HVR may be more reversible than the HVD (20).…”
Section: Discussionmentioning
confidence: 95%
“…The approach has been used recently to reveal ancestry associations with some complex disease traits in admixed populations (15,23,41,72), although it should be recognized that such associations reveal nothing direct about causal genetic mechanisms or evolutionary origins. Another limitation of this approach is that physiological traits can be sensitive to environmental effects, and it is well known that ventilatory control and pulmonary gas exchange systems are affected by developmental exposure to hypobaric hypoxia (17,10,70,20,63). For this reason, we studied Peruvian subjects who were born and raised at sea level (Lima, Peru).…”
mentioning
confidence: 99%
“…A exuberância deste processo adaptativo, isto é, do grau da resposta ventilatória ao estímulo hipóxi-co, apresenta grande variabilidade interindividual parecendo estar associada a diversos factores, tais como o fenótipo e genótipo (31,77). Deste modo, alguns estudos com populações nativas de regiões de elevada altitude (14,15,79), nomeadamente andinas e himalaínas, têm demonstrado que, comparativamente a sujeitos caucasianos residentes ao nível do mar, a sua resposta ventilatória à hipóxia não é tão exuberante. Este facto, influenciado por factores ontogenéticos e filogenéticos, parece reflectir um padrão de adaptação ventilatório característico, regulado pela importância da manutenção do equilíbrio ácido-base sanguíneo e por adaptações anatómicas específicas do sistema respiratório (31,55,56).…”
Section: Adaptações Ventilatóriasunclassified